FACTORS FOR THE DEVELOPMENT OF MEDIA COMPETENCE OF FUTURE PRACTICAL PSYCHOLOGISTS - Khomenko-Semenova, Larysa; Rudiaka-Petrychenko, Olha; Shapenko, Nataliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article analyzes the problems of media competence of future practical psychologists. The main elements, advantages and disadvantages of distance education are considered and analyzed, as well as the prospects of its development in the modern university are predicted. Based on the theoretical analysis of the research, it is proved that the development of media competence increases with the use of the latest information and communication technologies (ICT), educational trainings on media literacy. Based on the study of the problems of media competence development of future practical psychologists, we conducted a study on the Google Classroom educational platform using Blank Quiz. The sample was made by students of higher education of the I-IV courses of the Faculty of Linguistics and Social Communications of the National Aviation University, specialty 053 «Psychology» of the «Practical Psychology» educational program. The results of the study showed that most students have a sufficient level of media competence, but there is a need to provide the educational environment of the university with media educational platforms. According to the results of the survey, students pay attention to the need to modernize the approach to independent work in higher education, in particular, to increase the concentration of attention on tasks that involve critical analysis of texts, interpretation of media content. Ways of successful development of media competence of future practical psychologists are determined, which consist in involving media content in the educational process. The role of social networks is recognized, as the results of the study showed their importance both in educational activities and in everyday use; trainings and master classes on media literacy. At the same time, the role of the teacher in the inclusion of media content in the educational process of students of higher education is important